Helicobacter pylori Outer Membrane Vesicle Size Determines Their Mechanisms of Host Cell Entry and Protein Content - Turner, Lorinda; Bitto, Natalie J.; Steer, David L.; Lo, Camden; D’Costa, Kimberley; Ramm, Georg; Shambrook, Mitch; Hill, Andrew F.; Ferrero, Richard L.; Kaparakis-Liaskos, Maria (Frontiers in Immunology, 2018)
Gram-negative pathogens ubiquitously shed outer membrane vesicles (OMVs) that play a central role in initiating and regulating pathogenesis in the host. Due to their highly inflammatory nature, OMVs are extensively being examined for their role in mediating disease in addition to their applications in innovative vaccines. A key mechanism whereby OMVs mediate inflammation and disease progression is dependent on their ability to enter host cells. Currently, the role of OMV size on determining their mechanism of cellular entry and their protein composition remains unknown. In this study, we examined the mechanisms whereby OMV size regulates their mode of entry into epithelial cells, in addition to their protein cargo and composition. We identified that a heterogeneous sized population of Helicobacter pylori OMVs entered epithelial cells via macropinocytosis, clathrin and caveolin dependent endocytosis. However, smaller OMVs ranging from 20 to 100nm in size preferentially entered host cells via caveolin mediated endocytosis. Whereas larger OMVs ranging between 90 to 450nm in size entered host epithelial cells via macropinocytosis and endocytosis. Most importantly, we identified the previously unknown contribution that OMV size has on determining their protein content, as fewer and less diverse bacterial proteins were contained within small OMVs compared to larger OMVs. Collectively, these findings identify the importance of OMV size in determining the mechanisms of OMV entry into host cells, in addition to regulating their protein cargo, composition and subsequent immunogenicity. These findings have significant implications in broadening our understanding of the bacterial regulation of virulence determinants and immunogenic proteins associated with OMVs, their role in mediating pathogenesis and in refining the design and development of OMV-based vaccines.